Transient flow through a porous channel with ramped pressure gradient and velocity slip boundary condition - Jha, Basant K.; Yunus, Zainab Sa`id (Zielona Góra: Uniwersytet Zielonogórski)
A transient flow formation of an incompressible fluid through a horizontal porous channel assuming a ramped pressure gradient is considered with the velocity slip boundary conditions. The flow is a laminar flow caused by ramped pressure gradient along the flow direction.
Keywords: transient flow; velocity slip; ramped pressure gradient; Riemann-Sum approximation technique